Análise da implementação das ferramentas do Lean em micro e pequenas empresas - David, Guilherme Fenselau (Universidade do Vale do Rio dos Sinos, 2018)
This research presents the analysis of implementing Lean Manufacturing tools through the Industry+ Method. The method under study corresponds to a roadmap for deploying Lean tools (JIT toolkit - Just in Time) in micro and small enterprises. In this sense, the barriers to implementation of this method, its degree of adherence to the companies, as well as the perception of the consultants that have operationalized its implementation are unknown. The objective of this research is to identify these gaps, analyze them and propose improvements to increase the success rate. This work was elaborated in four stages: i) study and construction of a national and international theoretical reference on the subject; ii) a case study with eleven consultants who applied the Industry + Method, adding 147 companies consulted; iii) analysis of the barriers to implementation of Lean Manufacturing tools; iv) analysis of the results obtained. The case study makes use of Lawrence Bardin's techniques for analyzing the content of interviews. The results of the study present the support for implantation as the main barrier associated with the failure rate of the project in micro and small companies. It has been found that there are other barriers that negatively impact the success of the implementation. Improvement points and suggestions emerged from the literature and interviewees.
Keywords: Filosofia Lean Manufacturing; Implantação; Micro e pequena empresa; Método Indústria+; Lean Manufacturing philosophy; Implementation; micro and small enterprises; Industry+ Method